Influence of Surface Roughness on Interdiffusion Processes in InGaP/Ge Heteroepitaxial Thin Films. (1st January 2015) - Sophia, P. Joice; Attolini, G.; Bosi, M.; Buffagni, E.; Ferrari, C.; Frigeri, C.; Vad, K.; Csik, A.; Takáts, V.; Zolnai, Z.
Abstract : In the present work, we report on the study of InGaP/Ge heterojunctions grown by metal organic vapor phase epitaxy at different growth temperatures, with the aim of analyzing properties of the layer and interface between InGaP epilayer and germanium substrate. Secondary Neutral Mass Spectroscopy, Rutherford Backscattering Spectrometry, High Resolution X-Ray Diffraction, Transmission Electron Microscopy and Atomic Force Microscopy have been used to characterize the layers. The main goal of this work is to get information about diffusion processes of Ga, In, P in the substrate and of Ge in the epitaxial film. Since the interface roughness during sputtering and the effect of diffusion depends on the growth temperature, depth profiles measured experimentally were combined with surface roughness data in order to get more reliable information about diffusion profiles and the real depth distribution of elements in the interface.